The evolution of the cave's entrance of Bruniquel and consequences for its accessibility by early Homo neanderthalensis - K. Génuite; S. Verheyden; H. Camus; C. Burlet; M. Boudadi-Maligne; L. Bruxelles; H. Cheng; D. Cochard; S. Delaby; E. Fabre; C. Ferrier; C. Lézin; et al. (Quaternary Science Reviews, 2026)

Critical flicker fusion frequency: confounders and caveats - Thomas Muth; Jochen D. Schipke; Anne-Kathrin Brebeck; Sven Dreyer (European Journal of Applied Physiology, 2026)
Introduction Critical flicker fusion frequency (cFFF) measures visual perception, with higher values indicating better performance. It is widely used to assess the effects of breathing gases in diving and hyperbaric environments. Aim Identify confounders explaining inconsistent cFFF study results. Methods Four experiments using a manual flicker device in volunteers with healthy eyes: 1. cFFF was measured in 174 recreational divers to examine demographic effects. 2. One male diver was tested daily over 85 days. 3. In 28 divers, cFFF was measured before and after 5 min of normobaric oxygen. 4. In 24 divers, cFFF was tested with and without diving masks, plus a condition with diagonal flicker light on the mask. Results 1. Mean cFFF: 39.2 ± 5.1 Hz; decreased with age ( p < 0.001), no gender/BMI effect. 2. Mean: 43.4 ± 2.1 Hz; stable across lighting. 3. Thresholds differed by frequency order; minimal O₂ effect. 4. Masks had no effect, but diagonal light reduced cFFF ( p < 0.01). Conclusion cFFF varied by 13% across divers and 5% in a single diver. Age and observer-light geometry influenced results. Oxygen had minor impact. Findings support using age-specific norms and considering perceptual confounders in diving research.

Conservation genomics of an endangered montane amphibian reveals low population structure, low genomic diversity and selection pressure from disease - D. R. Trumbo; B. M. Hardy; H. J. Crockett; E. Muths; B. R. Forester; R. G. Cheek; S. J. Zimmerman; S. Corey‐Rivas; L. L. Bailey; W. C. Funk (Molecular Ecology, 2023)
Wildlife diseases are a major global threat to biodiversity. Boreal toads ( Anaxyrus [Bufo] boreas ) are a state‐endangered species in the southern Rocky Mountains of Colorado and New Mexico, and a species of concern in Wyoming, largely due to lethal skin infections caused by the amphibian chytrid fungus Batrachochytrium dendrobatidis ( Bd ). We performed conservation and landscape genomic analyses using single nucleotide polymorphisms from double‐digest, restriction site‐associated DNA sequencing in combination with the development of the first boreal toad (and first North American toad) reference genome to investigate population structure, genomic diversity, landscape connectivity and adaptive divergence. Genomic diversity ( π = 0.00034–0.00040) and effective population sizes ( N e = 8.9–38.4) were low, likely due to post‐Pleistocene founder effects and Bd ‐related population crashes over the last three decades. Population structure was also low, likely due to formerly high connectivity among a higher density of geographically proximate populations. Boreal toad gene flow was facilitated by low precipitation, cold minimum temperatures, less tree canopy, low heat load and less urbanization. We found >8X more putatively adaptive loci related to Bd intensity than to all other environmental factors combined, and evidence for genes under selection related to immune response, heart development and regulation and skin function. These data suggest boreal toads in habitats with Bd have experienced stronger selection pressure from disease than from other, broad‐scale environmental variations. These findings can be used by managers to conserve and recover the species through actions including reintroduction and supplementation of populations that have declined due to Bd .

Heart Rate Variability from Underwater Spiroergometry: How Meaningful? - Andreas Koch; Fabian Möller; Elena Jacobi; Thomas Muth; Clark Pepper; Uwe Hoffmann; Jochen D. Schipke (Journal of Science in Sport and Exercise, 2023)

Allelic diversity of three anthocyanin synthesis genes in accessions of native Solanum tuberosum L. ssp. tuberosum at the Potato Genebank of the Universidad Austral de Chile - J. L. Solís; J. Muth; J. Canales; C. Lizana; D. Pruefer; R. Riegel; A. Behn (Genetic Resources and Crop Evolution, 2022)

Why disease ecology needs life‐history theory: a host perspective - Andrés Valenzuela‐Sánchez; Mark Q. Wilber; Stefano Canessa; Leonardo D. Bacigalupe; Erin Muths; Benedikt R. Schmidt; Andrew A. Cunningham; Arpat Ozgul; Pieter T.J. Johnson; Hugo Cayuela (Ecology Letters, 2021)
When facing an emerging infectious disease of conservation concern, we often have little information on the nature of the host‐parasite interaction to inform management decisions. However, it is becoming increasingly clear that the life‐history strategies of host species can be predictive of individual‐ and population‐level responses to infectious disease, even without detailed knowledge on the specifics of the host‐parasite interaction. Here, we argue that a deeper integration of life‐history theory into disease ecology is timely and necessary to improve our capacity to understand, predict and mitigate the impact of endemic and emerging infectious diseases in wild populations. Using wild vertebrates as an example, we show that host life‐history characteristics influence host responses to parasitism at different levels of organisation, from individuals to communities. We also highlight knowledge gaps and future directions for the study of life‐history and host responses to parasitism. We conclude by illustrating how this theoretical insight can inform the monitoring and control of infectious diseases in wildlife.

Cyclodextrin Complexation for Enhanced Stability and Non-invasive Pulmonary Delivery of Resveratrol—Applications in Non-small Cell Lung Cancer Treatment - Xuechun Wang; Vineela Parvathaneni; Snehal K. Shukla; Dipti D. Kanabar; Aaron Muth; Vivek Gupta (AAPS PharmSciTech, 2020)

Sorafenib Loaded Inhalable Polymeric Nanocarriers against Non-Small Cell Lung Cancer - Snehal K. Shukla; Nishant S. Kulkarni; Pamela Farrales; Dipti D. Kanabar; Vineela Parvathaneni; Nitesh K. Kunda; Aaron Muth; Vivek Gupta (Pharmaceutical Research, 2020)

Recruitment tolerance to increased temperature present across multiple kelp clades - Arley F. Muth; Michael H. Graham; Christopher E. Lane; Christopher D. G. Harley (Ecology, 2019)
Kelp systems dominate nearshore marine environments in upwelling zones characterized by cold temperatures and high nutrients. Worldwide, kelp population persistence and recruitment success generally decreases with rising water temperatures coupled with low nutrients, making kelp populations vulnerable to impending warming of the oceans. This response to climate change at a global scale, however, may vary due to regional differences in temperature variability, acclimation, and differential responses of kelp species to changing conditions. Culture experiments were conducted on 12 eastern Pacific kelp taxa across geographic regions (British Columbia, central California, and southern California) under three nitrate levels (1, 5, and 10 μmol/L) and two temperatures (12°C and 18°C) to determine sporophyte production (i.e., recruitment success). For all taxa from all locations, sporophytes were always present in the 12°C treatment and when recruitment failure was observed, it always occurred at 18°C, regardless of nitrate level, indicating that temperature is the driving factor limiting recruitment, not nitrate. Rising ocean temperatures will undoubtedly cause recruitment failure for many kelp species; however, the ability of species to acclimatize or adapt to increased temperatures at the warmer edge of their species range may promote a resiliency of kelp systems to climate change at a global scale.

Otolith shape as a valuable tool to evaluate the stock structure of swordfish Xiphias gladius in the Indian Ocean - K Mahé; H Evano; T Mille; D Muths; J Bourjea (African Journal of Marine Science, 2016)

The genetic structure of a relict population of wood frogs - Rick D. Scherer; Erin Muths; Barry R. Noon; Sara J. Oyler-McCance (Conservation Genetics, 2012)

Characterisation of 22 polymorphic microsatellite loci for the Broadbill Swordfish, Xiphias gladius - H. Bradman; P. Grewe; J. Bourjea; D. Muths; B. Appleton (Conservation Genetics Resources, 2011)

Diversity in destinations, routes and timing of small adult and sub‐adult striped bass Morone saxatilis on their southward autumn migration - M. E. Mather; J. T. Finn; S. M. Pautzke; D. Fox; T. Savoy; H. M. Brundage; L. A. Deegan; R. M. Muth (Journal of Fish Biology, 2010)
Almost three‐quarters of the 46 young adult and sub‐adult striped bass Morone saxatilis that were acoustically tagged in Plum Island Estuary, Massachusetts, U.S.A., in the summer of 2006 were detected in one or more southern coastal arrays during their autumn migration. On the basis of the trajectories along which these M. saxatilis moved from feeding to overwintering areas, three migratory groups emerged. After leaving Plum Island Estuary, about half of the fish were detected only in a mid‐latitude array, Long Island Sound. The other half of the tagged fish were detected during autumn and winter in a more southern array, the Delaware Estuary. This latter group of fish may have used two routes. Some travelled to the Delaware Estuary through Long Island Sound while other fish may have taken a second, more direct, coastal route that did not include Long Island Sound. Consequently, a seemingly homogeneous group of fish tagged at the same time in the same non‐natal feeding location exhibited a diversity of southward movement patterns that could affect population‐level processes. These three groups that differed in overwintering location and migration route could be movement contingents with migratory connectivity.

Effects of Amphibian Chytrid Fungus on Individual Survival Probability in Wild Boreal Toads - DAVID S. PILLIOD; ERIN MUTHS; RICK D. SCHERER; PAUL E. BARTELT; PAUL STEPHEN CORN; BLAKE R. HOSSACK; BRAD A. LAMBERT; REBECCA MCCAFFERY; CHRISTOPHER GAUGHAN (Conservation Biology, 2010)
Chytridiomycosis is linked to the worldwide decline of amphibians, yet little is known about the demographic effects of the disease. We collected capture–recapture data on three populations of boreal toads ( Bufo boreas [Bufo = Anaxyrus] ) in the Rocky Mountains (U.S.A.). Two of the populations were infected with chytridiomycosis and one was not. We examined the effect of the presence of amphibian chytrid fungus (Batrachochytrium dendrobatidis [Bd]; the agent of chytridiomycosis) on survival probability and population growth rate. Toads that were infected with Bd had lower average annual survival probability than uninfected individuals at sites where Bd was detected, which suggests chytridiomycosis may reduce survival by 31–42% in wild boreal toads. Toads that were negative for Bd at infected sites had survival probabilities comparable to toads at the uninfected site. Evidence that environmental covariates (particularly cold temperatures during the breeding season) influenced toad survival was weak. The number of individuals in diseased populations declined by 5–7%/year over the 6 years of the study, whereas the uninfected population had comparatively stable population growth. Our data suggest that the presence of Bd in these toad populations is not causing rapid population declines. Rather, chytridiomycosis appears to be functioning as a low‐level, chronic disease whereby some infected individuals survive but the overall population effects are still negative. Our results show that some amphibian populations may be coexisting with Bd and highlight the importance of quantitative assessments of survival in diseased animal populations.

Pre-zygotic factors best explain reproductive isolation between the hybridizing species of brittle-stars Acrocnida brachiata and A. spatulispina (Echinodermata: Ophiuroidea) - D. Muths; D. Davoult; M. T. Jolly; F. Gentil; D. Jollivet (Genetica, 2010)

What is “fallback”?: metrics needed to assess telemetry tag effects on anadromous fish behavior - Holly J. Frank; Martha E. Mather; Joseph M. Smith; Robert M. Muth; John T. Finn; Stephen D. McCormick (Hydrobiologia, 2009)

Incomplete cryptic speciation between intertidal and subtidal morphs of Acrocnida brachiata (Echinodermata: Ophiuroidea) in the Northeast Atlantic - D. MUTHS; D. DAVOULT; F. GENTIL; D. JOLLIVET (Molecular Ecology, 2006)
The brittle‐star Acrocnida brachiata (Montagu) lives in sandy‐bottom habitat of both intertidal and subtidal zones along the coasts of the northwestern Europe. An allozyme frequency‐based survey (five enzyme loci) was combined with a mitochondrial (mt) COI haplotype analysis (598‐bp sequences) on 17 populations to trace back past colonization pathways from the actual population structure of the species. Both genetic markers display a sharp genetic break between intertidal (clade I) and subtidal populations (clade S). This break corresponds to an allele frequency inversion at three enzyme loci ( Hk , Pgm and Pgi ) and a deep divergence of about 20% in mtCOI sequences between most of the intertidal populations and other samples. The geographic distribution of clade I seems to be more restricted than clade S as it is absent from the intertidal of the eastern English Channel and North Sea and may be replaced by clade S in south Brittany. Applying previously published rates of mutation, divergence between the two clades is estimated to pre‐date 5 million years ago and may be due to allopatric speciation processes at the Mio–Pliocene transition. The occurrence of putative hybrids in a few localities, however, suggests incomplete cryptic speciation with secondary contact zones. The relative importance of colonization history vs. habitat specialization are discussed in the light of neutral evolution as tested from mtCOI gene sequences. While differential selection seems to have contributed little to the separation of the lineages, it may have played a role in the emergence of adaptive polymorphisms in the hybrid zone. Furthermore, congruent spatial patterns of differentiation were observed in both clades suggesting a recent increase in population size. These findings are in agreement with a recent expansion of the populations during or after the formation of the English Channel, from a southern refuge for the subtidal clade whereas the intertidal clade may have persisted further north. As previously suspected for a species with a very short pelagic larval phase, contemporary gene flow between distant or adjacent populations appears to be extremely reduced or even absent.

Construction and characterization of a plant transformation-competent BIBAC library of the black Sigatoka-resistant banana Musa acuminata cv. Tuu Gia (AA) - E. Ortiz-Vázquez; D. Kaemmer; H-B. Zhang; J. Muth; M. Rodríguez-Mendiola; C. Arias-Castro; Andrew James (Theoretical and Applied Genetics, 2005)